Analysing Aflatoxin Production Conditions in Feed Samples Using a Preparative Thin Layer Chromatography (TLC) Method - Abrahem, Sarra A. (Iraqi Journal of Science, 2022)
In this research, aflatoxins were produced, extracted, isolated, and purified in order to optimize the storage conditions of feed. Using a preparative thin layer chromatography (TLC) method, with commercially available plates of 1.5 to 2.0 mm, B1 aflatoxin was isolated from the feed samples of whole wheat, maize, and crushed rice, and the procedure was repeated four times. A purity value of 99 % for B1 aflatoxin was achieved and tested using spectrophotometric and chromatographic methods. As solvents, acetone:water (85:15l) was used for aflatoxin extraction from the feed sample, whereas methanol: water (50: 50) was used for trichothecenes extraction. The primary findings of this research indicate that B1 aflatoxin reached a maximum yield when coarsely crushed rice was inoculated with Aspergillus parasiticus at a temperature of 30C°, moisture level of 35%, and incubation duration of 7 days. The observations obtained from aflatoxins production process provide an insight regarding storage conditions that need to be avoided in order to reduce the incidents of feed contamination.